Maskot Desa Wisata yang Menyatukan Warisan Budaya Bandung - Karya Inovatif KUKERTA UIN SMH Banten Kelompok 29 - Putri Melani; Lughoh Khofifah; Muthia Magrina; Hilda Khaerunnisa; Agus Sukirno (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Bandung Village, which is rich in local traditions and culture, has launched the Dewi Sinyonya mascot as part of its tourism promotion strategy. This mascot, which is the work of KUKERTA UIN SMH Banten group 29 students, aims to connect the village's cultural heritage with the modern era. The name "Dewi Sinyonya" reflects the village's ambition to be known as a leading tourist destination, where "DEWI" means "Tourist Village" and "SINYONYA" refers to the legendary goldfish species that symbolizes good luck. This mascot wears a kiwari iket and pangsi shirt, and carries a bag woven with pandan leaves as a symbol of local craftsmanship. With its deep design and symbolism, Dewi Sinyonya not only functions as a visual icon, but also as a cultural representation that brings the heritage of Bandung Village to life. It is hoped that its presence will attract tourists to explore the beauty and richness of village culture, as well as strengthen local cultural identity in the modern era.